To Have the Best Interest at Heart: Analyzing the Match Between Laypersons’ Interests and Publication Activity in Psychology - Jonas, Mark; Bittermann, André; Chasiotis, Anita; Rosman, Tom (Frontiers in Psychology, 2022)
There is a growing public interest in science and, by extension, in psychology and human behavior. Yet, detailed investigations on whether psychological research activity matches lay interests are still scarce. In addition, while lay-friendly communication of research findings becomes continually more important, it is unclear which subfields of psychological research are particularly interesting to laypeople. To address these research gaps, we carried out an explorative study of psychological literature included in two large reference databases, one with a German (PSYNDEX), and one with international (PsycInfo) scope. The years of 2018–2020 were scanned for articles belonging to one of 20 topic areas assessed as most interesting by lay participants in a previous study. We determined and compared the share of empirical research and research syntheses for each topic area and database and computed rank correlations between lay interest and publication volume. Results suggest a positive relationship between lay interest and publication activity specifically for research syntheses. Additionally, topic areas associated with clinical psychology offered a large share of research syntheses, while other topic areas such as “Psychodynamics” or “Industrial & Organizational Psychology” encompassed a smaller share of syntheses. Finally, we outline perspectives for long-term monitoring of psychology-related lay interests. Thus, the present study connects academic activity with the public interest in psychology by identifying and quantifying research syntheses for topics garnering the most lay interest.